1957
DOI: 10.1017/s0007485300054201
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Larvae of the Large White Butterfly (Pieris brassicae (L.)) to Diets of Mineral-deficient Leaves

Abstract: The direct approach to the study of the food requirements of insects is to rear them on artificial diets. This has, however, proved difficult in the case of those normally feeding on living plants, although larvae of the European Corn Borer (Pyrausta nubilalis (Hb.)) have been raised successfully in this way (Bottger, 1942;Beck & Lilly, 1949). Changes in the food value of leaves may, nevertheless, be readily induced under controlled conditions by growing plants in sand or water culture. Studies on insect growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1960
1960
1982
1982

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…There was no indication whether phosphorus or some other substance whose abundance was correlated with that of phosphorus was the effective factor, but there were no marked differences between the two treatments in the amounts of any of the other elements shown in Table 11. Allen and Selman (1957) have reported that Pieris brassicae (L.) has a small larval weight and a long development period when reared on turnip leaves grown in a phosphorus-deficient medium whereas Dahms (1947) has reported that Blissus leucopterus (Say) laid more eggs when reared on seedling sorghum grown in a phosphorus-deficient medium. It may be that these two investigations were conducted on ranges of phosphorus content that were on opposite sides of an optimum.…”
Section: Discussionmentioning
confidence: 99%
“…There was no indication whether phosphorus or some other substance whose abundance was correlated with that of phosphorus was the effective factor, but there were no marked differences between the two treatments in the amounts of any of the other elements shown in Table 11. Allen and Selman (1957) have reported that Pieris brassicae (L.) has a small larval weight and a long development period when reared on turnip leaves grown in a phosphorus-deficient medium whereas Dahms (1947) has reported that Blissus leucopterus (Say) laid more eggs when reared on seedling sorghum grown in a phosphorus-deficient medium. It may be that these two investigations were conducted on ranges of phosphorus content that were on opposite sides of an optimum.…”
Section: Discussionmentioning
confidence: 99%